Prevalence and epidemiological aspects of depression in the elderly (Research, Society and Development, 2022)
The study aimed to identify the prevalence of depression in the Elderly Health outpatient clinic of a Medical Specialties Center (CEMEC), recognizing epidemiological aspects of elderly people with this disease. This was an observational, cross-sectional, descriptive and analytical research in the medical records of patients treated at CEMEC, which is part of the Unified Health System. genders), with the collection of data through a questionnaire, elaborated by the researchers, with the variables: medical record number, sex, age, marital status, occupation, religion and education. Medical records were analyzed and it was observed that the prevalence of depression in the studied population was 24.51%. Regarding gender, 18.71% were women and 5.81% men diagnosed with depression. Elderly people aged 60 to 69 years are the most affected, with 9.03%, the majority corresponded to those who declared themselves married, 37.84%, followed by widowers, 29.73% and, regarding occupation, 82.86% of patients with depression are retired. Thus, it is understood that the health team is attentive to the elderly regarding psychiatric problems to prevent, diagnose and adequately treat patients with depressive disorders, generating a better quality of life.